2021
DOI: 10.3390/ijms222011015
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Formation Mechanism of Antimicrobial Peptides Temporin B- and L-Induced Tubular Membrane Protrusion

Abstract: Temporins are a family of antimicrobial peptides (AMPs) isolated from frog skin, which are very short, weakly charged, and highly hydrophobic. They execute bactericidal activities in different ways from many other AMPs. This work investigated morphological changes of planar bilayer membranes composed of mixed zwitterionic and anionic phospholipids induced by temporin B and L (TB and TL) using all-atom and coarse-grained molecular dynamics simulations. We found that TB and TL fold to α-helices at the membrane s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 62 publications
2
5
0
Order By: Relevance
“…Studies on glass-supported phospholipid bilayers revealed that the interactions of temporin B with these model membranes results in the segregation of membrane-bound peptides and formation of lipid fibrillar protrusions [ 70 ], suggesting that the interaction of peptides with lipids drives membrane shape transformations. Recent studies performed using all-atom and coarse-grained molecular dynamics simulations aimed at investigating the interaction of temporin B with mixed zwitterionic and anionic phospholipids membranes support previous experimental results, confirming the ability of temporin B to produce clusters on the membrane surface and promote the extrusion of lipids [ 71 ].…”
Section: Temporins From Ranasupporting
confidence: 63%
“…Studies on glass-supported phospholipid bilayers revealed that the interactions of temporin B with these model membranes results in the segregation of membrane-bound peptides and formation of lipid fibrillar protrusions [ 70 ], suggesting that the interaction of peptides with lipids drives membrane shape transformations. Recent studies performed using all-atom and coarse-grained molecular dynamics simulations aimed at investigating the interaction of temporin B with mixed zwitterionic and anionic phospholipids membranes support previous experimental results, confirming the ability of temporin B to produce clusters on the membrane surface and promote the extrusion of lipids [ 71 ].…”
Section: Temporins From Ranasupporting
confidence: 63%
“…For amphipathic α-helix peptides, several models explain how they work. The barrel pore model ( Figure 2 ) in which the amphipathic α-helix creates vertical pores across the membrane and peptides accumulate in barrel-shaped aggregates showing water-permeable and transmembrane-oriented pores [ 32 , 33 ].…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%
“…The formation of a transmembrane water-permeable pore results from the association of several AMP molecules with lipid heads in a toroidal pore model ( Figure 3 ) [ 33 ].…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Another method is introducing unnatural amino acids 20 or Nterminal amidation, 21 glycosylation, 22 and incorporating D-type amino acids in the peptide sequence 23 to enhance stability and reduce cytotoxicity. Moreover, optimizing antibacterial activity can be achieved through sequence splicing, enhancing charge, 24 increasing hydrophobicity, 25,26 and improving amphiphilicity. 18 The Abaecin, discovered in Apis mellifera, is a proline-rich AMP comprising 34 amino acids with 10 prolines (29%) and devoid of cysteine residues.…”
Section: ■ Introductionmentioning
confidence: 99%